Knowledge, attitude, and practices toward sun exposure and use of sun protection among non-medical, female, university students in Saudi Arabia: A cross-sectional study - Reema Ruddah Almuqati; Ali Saeed Alamri; Nawal Ruddah Almuqati (Wolters Kluwer, 2019)
Excessive unprotected sun exposure is a significant risk factor for skin damage and skin cancers. In recent decades, the incidence of skin cancer has increased dramatically worldwide, reaching epidemic proportions. Skin cancer is the most common type of cancer worldwide, and the ninth most common malignancy in Saudi Arabia. Sun protection is a key primary preventive strategy against skin cancer and skin damage induced by sun exposure.Herein, a cross-sectional study was made to evaluate the knowledge, attitude, and practices toward sun exposure, and the use of sun protection among non-medical female students on the Sulaymaniyah campus of the King Abdul-Aziz University. Also, we identified the reasons that prevented the students from using sun protection measures. A special-designed, self-administered questionnaire was applied on a sample size of 501 students. We found that most students were aware of the risks of unprotected sun exposure. Nevertheless, a view of sunscreen as harmful was reported (34.1%). Seeking shade and wearing protective clothing were the most used sun protection methods (58.1% and 43.1%, respectively). Sunscreen users made up only one third of our sample (23.6%). However, the majority of students (64.9%) did not know about the sun protection factor of sunscreen products. Discomfort felt on the skin was the most commonly reported reason for avoiding the use of sunscreen (40.7%). When comparing our study with Western studies, we found a high level of awareness among our sample of students. Significant differences in the attitude toward the application of suntan and sun protection products might be due to differences in cultural background. Our results spotted the need for future health education programs for our society that focus on the significant importance of sunscreen, as well as the correct methods of application. Keywords: Sun exposure, sun protection, sunscreen